Microbiological characterization of food handlers in school canteens - Gomes, Diana (2018)
Food-borne substances are a major concern of Public Health, given that food can be the source of various hazards (biological, physical and chemical). Approximately 20% of outbreaks of foodborne illness are associated with the personal hygiene of food handlers. The personal hygiene of manipulators is one of the best ways to block bacterial contamination and its extension to new areas. To evaluate the microbiological profile of the hands of food handlers in school canteens of the northern region of Portugal during 2016 and to verify the efficiency of the hygiene processes.